Modernization of Arts Education Paradigm by the Principle of Historical Continuity - Matonis, Vaidas (Pedagogika, 2013)
The purpose of the article is to show how the principle of historical continuity could be realized in order to make educational process more integral and purposeful. Research reveals relevance of historical continuity to the valuable forms of human’s spiritual activity. Main ideas which are developed in the article are based on the principles of the cultural policy elaborated by M. Lukšiene. The author of the article established a goal to evaluate art as a means to educate the sense and/or understanding of historical continuity, by the same token elevating perception of artworks to the metacognitive level and enlarging the field of historical and cultural contexts. Material of the investigation is laid by invoking the philosophical analysis of socio- and psychocultural phenomena and their impact on modernization of arts education. The role of the historical continuity and cultural awareness have activated during the last decades after the method of interpretation had intensified in valuable forms of human spiritual activity (moral, politics, aesthetics). So after such qualities of the works of art as depiction and/or craftsmanship had depreciated, the interpretation of the works of art and even the evaluation of interpretations sets in more and more robustly. In the presents of such or other contradictions the reform of European education has rippled by various different waves. As a result, the competence of democratic culture which enables the values, including artistic values, of democratic culture to implant to the attitudes of learners becomes the most essential orientation for teacher education. Development of democratic culture in EU defies such aspects of activity as knowledge and understanding of human rights, democratic participation and especially the development of competence for engaging in a meaningful and open - minded intercultural dialogue. Author is convinced that in order to realize and promote these ideas they should be accompanied by the development of the competence of dialogue with the past. Development of the competences of historical continuity and cultural context is increasing by mastering the ideas of great thinkers on education, including arts education, and helps to impersonate one of the most important domains of cultural heritage – educational potential of culture. In other words, historical continuity and cultural context are such core principles and values which can enable the development of the competence of full-rate intercultural dialogue. In case of arts education, when the paradigm of artistic thinking is rapidly changing, it is evident that an integrated history of artistic education should be developed. The main role of such academic course is not only to reveal cultural peculiarities of different countries but also to show the reasons of unequal educational power of different arts in different epochs. The role of historical continuity and cultural context is growing according to the development of digital technologies which are changing social conditions and possibilities of traditional artistic functions. Just the history of art and ideas of artistic education could balance both historical continuity of social artistic functions and involve learners into dialogue with the past.